2020
DOI: 10.1007/s00216-019-02349-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Raman spectroscopy for the analysis of plasma/serum in the liquid state: recent advances

Abstract: There is compelling evidence in the literature to support the application of Raman spectroscopy for analysis of bodily fluids in their native liquid state. Naturally, the strategies described in the literature for Raman spectroscopic analysis of liquid samples have advantages and disadvantages. Herein, recent advances in the analysis of plasma/serum in the liquid state are reviewed. The potential advantages of Raman analysis in the liquid form over the commonly employed infrared absorption analysis in the drie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 103 publications
0
29
0
Order By: Relevance
“…Figure 5 gives an overview of basic Raman spectroscopy. The reason why Raman spectroscopy is preferred is that it has high sensitivity to detect tiny changes with a molecular size of 1 µm [81,82]. The general advantages of Raman spectroscopy are higher depth penetration compared to mid-infrared spectroscopy, being less sensitive to temperature changes compared to OCT, wide application and high specificity [77].…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Figure 5 gives an overview of basic Raman spectroscopy. The reason why Raman spectroscopy is preferred is that it has high sensitivity to detect tiny changes with a molecular size of 1 µm [81,82]. The general advantages of Raman spectroscopy are higher depth penetration compared to mid-infrared spectroscopy, being less sensitive to temperature changes compared to OCT, wide application and high specificity [77].…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…[9][10][11][12][13][14] Raman spectroscopy is a well-documented spectrographic method of examining the molecular composition of both solids and solutions. 3,9,13,15,16 When examining even dilute and complex aqueous solutions (such as urine), 3,[9][10][11][12][13][15][16][17][18][19][20] Raman spectroscopy may take on the order of seconds to generate spectral data, with minimal spectral interference from water. Analysis of aqueous solution spectra involves data transformation in the form of baseline correction, truncation, normalization, and statistical processing.…”
Section: Introductionmentioning
confidence: 99%
“…It can thus potentially guide the identification of new biomarkers of cellular events, or recognition of phenomena not visible using other, for example fluorescence based techniques [9] . These techniques have been extensively explored to differentiate between healthy and diseased samples for diagnostic applications [10] , [11] , [12] , [13] , and recent studies using Raman and IR absorption spectroscopy have demonstrated great potential for their use with liquid biopsies samples [14] , [15] , [16] , [17] .…”
Section: Introductionmentioning
confidence: 99%